Impact of a mass vaccination campaign against Serogroup B meningococcal disease in the Saguenay-Lac-Saint-Jean region of Quebec four years after its launch. Issue 31 (18th July 2019) - Deceuninck, G.; Lefebvre, B.; Tsang, R.; Betala-Belinga, J.F.; De Serres, G.; De Wals, P.
Abstract: In the Saguenay-Lac-Saint-Jean region of Quebec, 83% of the population ≤20 years (n ≅ 59, 500) was immunized in 2014 with the four-component Serogroup B meningococcal vaccine to control a long-lasting outbreak caused by a virulent ST-269 Serogroup B Neisseria meningitidis clone. Following the campaign, invasive meningococcal B disease (B-IMD) incidence fell sharply in the target population from 11.4/100, 000 in 2006–2014 to 0.4/100, 000 in 2014–2018 (p < 0.0001). Five B-IMD cases occurred in the region from July 2014 to June 2018, including one vaccinated child, one unvaccinated young adult and 3 unvaccinated elderly adults. Estimate of direct vaccine protection was 79% [95%CI:−231%;99%]. The overall campaign impact in the region taking into account the decrease in B-IMD incidence at provincial level was a 86% [95%CI:−2%;98%] decrease in B-IMD risk. The campaign impact was mostly seen in the target age-group suggesting no herd effect among unvaccinated older adults.